Implementation of Good Corporate Governance (GCG) on the Performance of Employees of the Belawan Customs Supervision and Service Office in Medan, North Sumatra - amy teuku; zulkifli taib (Universitas Dharmawangsa Medan, 2026)
A strategic factor to improve the performance of public sector organizations is the implementation of Good Corporate Governance (GCG). The purpose of this study was to look at how transparency (X1), accountability (X2), responsibility (X3), and independence (X4) affect organizational performance (Y). This study was conducted with a quantitative approach, with a sample of 133 respondents and analyzed using multiple linear regression. The results showed the regression equation as follows: Y = 2.135 + 0.312X1 + 0.284X2 + 0.256X3 + 0.298X4. According to the t-test, transparency (t = 3.842; p = 0.000), accountability (t = 3.517; p = 0.001), responsibility (t = 3.24; p = 0.002), and independence had a positive and partially significant impact on organizational performance. The value of Fcal = 45.673 with p = 0.000 (<0.05) indicates that all independent variables affect the company's performance simultaneously. A determination coefficient (R2) of 0.588 indicates that GCG variables may be responsible for 58.8% of organizational performance variations, while 41.2% are due to other factors outside the model. The result is that the correct implementation of GCG can result in continuous improvement in organizational performance.